2012
DOI: 10.1159/000340046
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Laryngeal Findings on Acoustic Parameters of Patients with Laryngopharyngeal Reflux

Abstract: Objectives: To identify the effects of laryngopharyngeal reflux (LPR)-related laryngeal findings on objective voice parameters. Methods: Two hundred and thirty patients clinically diagnosed as having LPR and 48 healthy controls were included. The reflux finding score was determined for each subject via videolaryngoscopy. The acoustic parameters evaluated were jitter, shimmer, noise-to-harmonic ratio and Voice Turbulence Index (VTI). Results: Shimmer and VTI showed statistically significant differences between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 26 publications
2
16
0
Order By: Relevance
“…Compared with other laryngeal diseases, granuloma was detected more frequently in the LPR group [20]. A recent study revealed that reflux was an independent factor affecting the resolution of granuloma [15].…”
Section: Discussionmentioning
confidence: 83%
“…Compared with other laryngeal diseases, granuloma was detected more frequently in the LPR group [20]. A recent study revealed that reflux was an independent factor affecting the resolution of granuloma [15].…”
Section: Discussionmentioning
confidence: 83%
“…Indeed, among the 4 studies that compared acoustic measurements between LPR and healthy participants, all reported different results. Percentage shimmer and percentage jitter were respectively identified as significantly different between LPR and healthy participants in three 10,11,13 and two 11,12 studies. The majority of these studies did not find substantial differences in the values of F0 and NHR between patients with LPR and healthy controls, which corroborates our findings.…”
Section: Discussionmentioning
confidence: 91%
“…7 Thus, some 20 prospective trials were conducted to assess the voice quality changes throughout treatment, 8,9 and only 5 case-control studies assessed voice quality impairments in patients with LPR compared to healthy participants. [10][11][12][13][14] Among the case-control studies, no study assessed voice quality with multidimensional approach including, at least, subjective, perceptual, aerodynamic, and acoustic evaluations. Moreover, the trials that measured objective voice quality reported mixed results, [10][11][12][13] which are probably due to methodological measurement discrepancies between studies.…”
Section: Introductionmentioning
confidence: 99%
“…Increased jitter and shimmer may reflect degenerative changes in laryngeal tissue but shimmer seems to be a more sensitive parameter than jitter in LPR patients. [13,18,19,20] The HNR changes in LPR patients were shown as well. Some authors found statistically significant changes for HNR values [18,19,21] but others did not find any differences.…”
Section: Discussionmentioning
confidence: 95%
“…[13,18,19,20] The HNR changes in LPR patients were shown as well. Some authors found statistically significant changes for HNR values [18,19,21] but others did not find any differences. [18] On the other hand, it is still controversial whether voice parameters improve with medical treatment or not.…”
Section: Discussionmentioning
confidence: 95%